The role of recruitment in public service reform in Uzbekistan - Rasulov, Sh (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article is devoted to the study of the process of reforming public service in Uzbekistan, the place of selection of personnel in this area, the analysis of its achievements and shortcomings. The focus will be on the urgent problems of the formation of a modern model of public service in the country